EFEKTIVITAS AROMATERAPI LAVENDER DALAM MENURUNKAN NYERI DAN KECEMASAN PADA PASIEN PRE OPERASI FRAKTUR FEMUR DI RS ORTOPEDI PROF. DR.R SOEHARSO SURAKARTA - Yuli Widyastuti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2013)
Fracture is a potential or actual threat to the integrity of the person that will experience physiological and psychological disorders that can cause a pain response. The pain can arise in almost every area of the fracture.Fractures apart from causing pain can also cause anxiety. Anxiety (anxiety) is a psychological response to stress containing physiological and psychological components. Surgery or surgery is an experience that can have disastrous anxiety. The role of the nurse is a non pharmacological manejemen one using aromatherapy. Inhalingthe scent of lavender that help us to feel relaxed. Additionally Lavender is believed to help create a balance of body and mind. Study aimed lavender aromatherapy effectiveness in reducing pain and anxiety in patients withpreoperative femoral fracture in RS.Prof.DR.R. Soeharso Surakarta. Research using experimental research designs to approach pre-test and post-test only with the control group. Samples with accidental sampling.Independent variables: Aromatherapy lavender, dependent variables: pain and anxiety. Paired t test with a value of 0,000 pain (p <0.05), paired t test anxiety with significancy value of 0.000 (p <0.05), the value of pain unpaired t test with 0,000 significancy (p> 0,05). Unpaired t test anxiety 0.021 (p <0,05). Conclusions significant difference pain levels before and after aromatherapy lavener, there is a significant difference in anxiety levels before and after aromatherapy lavender, there are significant differences in the level of pain intervention and control groups, no significant difference in anxiety levels between the intervention andcontrol groupsKeywords: Lavender Aromatherapy, pain, Anxiety, femoral fracture